The Quest for Exciting Knowledge: Developments in Figurational Sociological Research on Sport and Leisure. - Malcolm, Dominic; Mansfield, Louise (Política y Sociedad, 2013)
This paper provides a thematic and developmental review of figurational sociological research on sport and leisure. It demonstrates how Elias’s main theoretical principles have been incorporated in this work and it uses ideas from Norbert Elias’s sociology of knowledge to explain how the emphasis on these principles has changed over time. Specifically, the paper identifies three overlapping stages in the construction of this body of knowledge and argues that a focus on violence has gradually diminished. The paper argues that this trend is both a consequence of the increasing availability of a broader range of Elias’s texts, but also due to social relations in the field, as latter generations of researchers find emotional gratification in expanding into new research agendas. The paper concludes by demonstrating the potential applicability of Elias’s theoretical principles to some of the most significant social issues of the twenty first century.